Factors Affecting Safe Sex Behavior Among Female Sex Workers in Surakarta, Central Java - Saras Vati Manvatarini Sugma; Aris Sudiyanto; Argyo Demartoto (Masters Program in Public Health, Sebelas Maret University, 2018)
Background: Earlier studies often focus solely on clients as female sex worker (FSW) risky sexual partners, ignoring the possible risks FSWs face from steady sex partners. Thus, further study is needed identifying strategies to reduce the potential increased risk of HIV/STI transmission between FSWs and their steady partners. This study aimed to determine factors affecting safe sex behavior among female sex workers in Surakarta, Central Java.Subjects and Method: A cross-sectional study was conducted in Banjarsari, Surakarta, Central Java, from April to May 2018. A sample of 134 female sex workers was selected by simple random sampling. The dependent variable was safe sex behavior. The independent variables were subjective norm, perceived behavior control, intention, attitude, education, and age. The data were collected by questionnaire and analyzed by path analysis.Results: Safe sex behavior increased with strong intention (b= 0.08; SE= 0.04; p=0.041). Safe sex behavior indirectly increased with older age, positive attitude, positive subjective norm, and strong perceived behavior control.